Diseño de un plan de marketing para la empresa Doopler distribuidores Cía. Ltda. Importadores y comercializadores de cortinas de fibra sintética ubicada en la ciudad de Quito. - Venegas Campaña, Fanny Gabriela (2013)
The following research paper will analyze the impact that the company Cia Ltd. Distributors Doopler will have once it implements the marketing plan which adjust to needs and reality that is going through. It is precise noted that the company Doopler is relatively new on the market, nevertheless in the growth that it has had in recent years it has noticed the lack of a marketing plan, for this it requires to carry out a transformation, that means that the company must define its strategies and actions which let to react and deal with a market that is becoming more competitive.